Investigating the ability of taxpayers to determine the income tax consequences of cryptocurrency transactions in South Africa - Vumazonke, Namhla (College of Accounting, 2022)
In 2018, the South African Revenue Service (SARS) issued a media statement providing guidance for the first time to South African citizens on the taxation of cryptocurrency transactions. The SARS media guidelines indicate that the normal income tax rules of the South African Income Tax Act will apply to cryptocurrency transactions and that cryptocurrency gains or losses must be declared as part of taxable income. The purpose of this research study was to investigate the ability of South African taxpayers to determine the income tax consequences of cryptocurrency transactions using the SARS media guidelines. Previous research has focused on establishing the theoretical income tax consequences of cryptocurrency transactions, rather than on the ability of taxpayers to determine those consequences. The study made use of both doctrinal and quantitative research methods to address the research questions. Using doctrinal research, in-depth document analysis was performed to benchmark the SARS media guidelines to that of selected tax authorities, to ascertain the completeness of this guidance. Quantitative data was collected through a cross-sectional survey questionnaire, to test the ability of participants to determine the income tax consequences of cryptocurrency transactions. This study found that the SARS media guidelines did not comprehensively address all the cryptocurrency transactions considered by the guidelines of the other selected tax authorities examined. The SARS media guidelines did not have a statistically significant effect on the participants' ability to determine the income tax consequences of the cryptocurrency transactions presented to them. However, the tax literacy level of participants was found to influence their understanding of the income tax consequences of cryptocurrency transactions, particularly in respect of those transactions not addressed by the SARS media guidelines. These findings support the recommendation that SARS provide more comprehensive guidance to taxpayers, and should focus on improving the tax literacy of taxpayers in general and, with respect to cryptocurrency transactions.